Standardy a kwestia aktywności firm w ograniczaniu ryzyka w łańcuchach dostaw - Maternowska, Małgorzata (Standards Versus the Problem of the Activity of Companies in Limiting the Risk in Supply Chains, 2008)
Overly standards are commonly thought to discourage parties from engaging in socially desirable activities. It is showed in this article that it is not true in a situation when legal standards are enforced by liability for negligence but it is, however, true when the adherence to the standards is required by the regulatory system.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 117-123